Predictive value of haematologic parameters in diagnosis of testicular torsion: Evidence from a systematic review and meta‐analysis. (28th November 2019) - Zhu, Jun; Song, Yuxuan; Chen, Guangyuan; Hu, Rui; Ou, Ningjing; Zhang, Wei; Liang, Zhen; Liu, Xiaoqiang
Abstract: To compare the difference of mean platelet volume (MPV), platelet lymphocyte ratio (PLR), neutrophil–lymphocyte ratio (NLR), platelet (PLT) and leucocyte between testicular torsion (TT), epididymo‐orchitis and healthy controls and further evaluate predictive values of these haematologic parameters in diagnosis and the differential diagnosis of TT. Databases were systematically retrieved, and reference search was also conducted manually. We applied Stata software 12.0 to perform a systematic review and meta‐analysis. Ultimately, five case–control studies with 672 participants were recruited for analyses. Pooled analyses indicated that TT patients had lower NLR (WMD = −1.66, 95% CI = −3.25 to −0.06) and PLT (WMD = −27.39, 95% CI = −48.03 to −6.75) compared to epididymo‐orchitis patients. In the meantime, TT patients had higher NLR and leucocyte than healthy controls ( p < .05). That is to say, when a man develops TT, his NLR and leucocyte will rise up but his NLR will not reach the level of epididymo‐orchitis. To sum up, NLR, PLT and leucocyte were vital factors for TT diagnosis. Leucocyte is an useful parameter for diagnosing both TT and epididymo‐orchitis, but it cannot be used in differentiating the two diseases. NLR is beneficial parameter for differential diagnosis between TT and epididymo‐orchitis. PLT can also be utilised in differential diagnosis among young patients.